2018
DOI: 10.1186/s12900-018-0087-2
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of a human myelin protein P2 portal region mutant indicate opening of the β barrel in fatty acid binding proteins

Abstract: BackgroundMyelin is a multilayered proteolipid sheath wrapped around selected axons in the nervous system. Its constituent proteins play major roles in forming of the highly regular membrane structure. P2 is a myelin-specific protein of the fatty acid binding protein (FABP) superfamily, which is able to stack lipid bilayers together, and it is a target for mutations in the human inherited neuropathy Charcot-Marie-Tooth disease. A conserved residue that has been proposed to participate in membrane and fatty aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(71 citation statements)
references
References 62 publications
10
61
0
Order By: Relevance
“…Anisotropy analysis of the structure (Figure 1e) shows an overall directionality of atomistic anisotropy, which could be related to functional open-close movements in the protein. Opening of the β barrel is thought to be central to ligand entry and egress, and could play a role in lipid membrane binding [18]. C-H...O bonds between side chains and main-chain carbonyl moieties are also frequently observed at the ends of secondary structure elements ( Figure 3).…”
Section: Pdb Entry 6s2m 6s2smentioning
confidence: 99%
“…Anisotropy analysis of the structure (Figure 1e) shows an overall directionality of atomistic anisotropy, which could be related to functional open-close movements in the protein. Opening of the β barrel is thought to be central to ligand entry and egress, and could play a role in lipid membrane binding [18]. C-H...O bonds between side chains and main-chain carbonyl moieties are also frequently observed at the ends of secondary structure elements ( Figure 3).…”
Section: Pdb Entry 6s2m 6s2smentioning
confidence: 99%
“…Knowledge of how ligands enter the cavity is important for manipulating FABP's function by blocking the ligand entrance. Previous molecular dynamics (MD) studies suggested three possible ligand entry sites for ligand and water to enter into or exit from the protein cavity: E I , located in the cap region involving the second α-helix (α2) and βC-βD and βE-βF turns; E II , the gap between βD and βE; and E III , in the area around the N-terminus (5)(6)(7)(8). Very recently, our studies on human intestinal FABP (hIFABP) have showed that opening the cap by swinging the two helices away from the barrel is dispensable for ligands to enter the cavity, and further demonstrated the existence of a minor conformational state that undergoes transient local unfolding in α2 on sub-millisecond timescale and thus provides a temporary opening in the E I region for ligand entry (9).…”
Section: Introductionmentioning
confidence: 99%
“…Recent MD simulations on human heart FABP show that the gap between βD and βE can open to become significantly wider (5,8). In addition, MD simulations on a human myelin protein P2, which is a member of the FABP superfamily, indicates that a large-scale opening of the barrel between βD and βE can occur through flapping βE and βF out (7). Upon this opening, the internalized cavity becomes accessible by ligands.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of the three functionalities allows the experimenter to predict the influence of mutation of central residues on local protein flexibility. RINspector has been used in different research projects to help in the identification of important residues in proteins that may be located at their core or surface, alone or in a complex (Brysbaert et al., ; de Ruyck et al., ; Laulumaa et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…These structures can be used for modeling at different levels, like homology modeling, protein-ligand docking, protein-protein docking, dynamic predictions, and simulations, or used to identify regions or residues of interest that may lead to mutagenesis experiments or be employed for targeted drug design. We have recently developed a tool called RINspector (Brysbaert, Lorgouilloux, Vranken, & Lensink, 2017, 2018, the goal of which is to identify key residues in a structure that are amenable to mutagenesis experiments. It is included as an app in the Cytoscape network visualization and analysis software (Shannon et al, 2003;Su, Morris, Demchak, & Bader, 2014), accessible through its apps manager.…”
Section: Introductionmentioning
confidence: 99%